El transfondo teórico-ideológico de la «libertad civil» y su eficacia - Ruipérez Alamilo, Javier (Teoría y Realidad Constitucional, 2007)
The preoccupation about the conciliation between Freedom and Democracy has always been present in the political thought along History. Is for this reason why this antinomy is been tried to be solved from several approaches from classical Greece to our days. It was the rise of the liberal Constitutional State which made real both premises but from an approach in which both concepts act like characteristic of two very different frames: the one of the civil society and the one of the State, so that Freedom that acts in the first one, conditions absolutely to the second. But certainly Freedom and Democracy are, in essence, complementary and inseparable terms, because none of them can be understood without the other, and their independent fulfilment would be impossible at all.